Social support campaign as an effort to fulfill psychological needs in pregnant, childbirth, and postpartum mothers - Sundari, Sri Wahyuni; Windiyani, Winda; Novayanti, Noorhayati; Ratri, Ratni; Purnamasari, Fitri; Sri, Shifa (Universitas Muhammadiyah Magelang, 2025)
The periods of pregnancy, childbirth, and postpartum are physically and emotionally challenging times for mothers and families, making adequate social support crucial for maternal recovery and family well-being. This campaign aimed to increase the awareness and knowledge of families and the community regarding the importance of emotional and physical support during these periods. Implemented through outreach, distribution of educational materials, and involvement of family members, the program showed a 41% increase in participants' knowledge regarding social support. The campaign proved effective in enhancing participants' understanding of mothers' vulnerable conditions and the positive and negative impacts of social support, which is expected to contribute to improving the well-being of mothers and families.